IMPROVING STUDENTS’ ENGAGEMENT IN WRITING LESSONS FOR NON-ENGLISH MAJOR STUDENTS USING TASK-BASED LANGUAGE TEACHING - Vo, Thi Hong Le; Tran, Xuan Trang; Chowdhury, Raqib (VNU Journal of Foreign Studies, 2025)
Abstract: Writing skills have always been perceived as difficult for English as a Foreign Language (EFL) learners in higher education. Studies (Vo, 2021; Huang, 2018; Zhang, 2016) have found that EFL students often commence tertiary education with an elementary level of English, which contributes to these challenges. In addition, a lack of confidence in writing results in demotivation in learning English. In line with recent empirical scholarship on EFL, Task-based Language Teaching (TBLT) is proposed as an effective approach that facilitates both the teaching of communicative skills and engagement through the use of the target language and tasks in an authentic and context-sensitive manner for EFL. Specifically, this study critically explores how adapting such a teaching method can help teachers and students nurture and improve their writing skills in English. Drawing on a quasi-experimental design involving 60 learners, it examines the extent to which TBLT can help improve writing skills for non-English major students at a Vietnamese university. The findings indicate that the implementation of TBLT tasks in writing lessons resulted in significant improvements in students’ writing performance. The study discusses participants’ statements in the experiment to better understand the perceptions of the effectiveness of this pedagogical approach.